Thermoeconomic performance of a CO2 heat pump for space and water heating of a 4-bedroom house in the South of England - Qayyum, Usman; Tassou, Savvas A; Torrens, Debarati; Tavares, Jose (Building services engineering research & technology, 2025)
Heat pumps are considered a key technology for the decarbonisation of space and water heating in domestic dwellings in the UK. Heat pumps that employ high-temperature working fluids such as CO2 have the potential to be used in retrofit applications. This paper presents the characteristics of a CO2 heat pump developed at Brunel University of London and the simulation results of its application to provide space and domestic hot water heating in a well-insulated four-bedroom semi-detached house with four occupants. The heating system is assumed to employ water thermal energy storage. Analysis has shown that storage volumes between 200 L and 300 L can satisfy the space temperature control requirements of the domestic dwelling if a heat pump capacity of 4.5 kW at 7°C ambient temperature and 60°C water flow temperature is employed. A comparison of the heat pump with a gas boiler reveals that with current gas and electricity prices, running costs for the heat pump can be 91% higher and CO2 emissions 40% lower than those of the gas boiler. Further design and control optimisation of the heat pump is expected to reduce both its running costs and CO2 emissions. Practical application This paper examines the practical application of a 4.5 kW heat pump with water thermal energy storage for domestic heating. The system operates efficiently at 7°C ambient and 60°C water flow temperatures, and can be retrofitted in two-thirds of UK homes without upgrading radiators. For a four-bedroom house, 200–300 L thermal storage volumes are optimal. While running costs are 91% higher than a gas boiler, the heat pump reduces CO2 emissions by 40%, offering a more sustainable heating solution.